Pulmonary arteriovenous malformation diagnosed by point-of-care ultrasound: a case report and review of the literature - Malqui-Huamán, Christian (2026)
We present the case of a 72-year-old woman diagnosed with arterial hypertension and mild cognitive impairment; she also had a history of cerebral infarction. The patient was admitted due to progressive dyspnea of uncertain etiology, with a six-month onset. The initial clinical assessment and laboratory tests did not establish the diagnosis. The persistence of dyspnea, with gasometric evidence of hypoxemia and an increased alveolar-arterial gradient, prompted further evaluation, which identified—via bedside Doppler pulmonary ultrasound—a subpleural vascular structure in the posterior basal region of the left lung consistent with an arteriovenous malformation. The finding was confirmed with conventional imaging studies. Finally, embolization of the lesion was performed with a good clinical outcome.